2019
DOI: 10.1002/lary.28139
|View full text |Cite
|
Sign up to set email alerts
|

Cost of treating recurrent respiratory papillomavirus in commercially insured and medicaid patients

Abstract: Objectives: The study objective was to estimate the first 2 years' direct costs of treating new cases of juvenile-onset and adult-onset recurrent respiratory papillomatosis (RRP) and determine the predictors of treatment costs.Methods: Cases were patients diagnosed with RRP in commercial insurance claims in 2011-2014 and Texas Medicaid in 2008-2012 for treatment of RRP. Controls were patients without a diagnosis of HPV-related cancer or RRP, matched with cases by age, sex, geographic area, date of diagnosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…22 The fiscal implications of RRP too are immense, with one study showing greater than $60,000 in a two-year cost difference for patients with RRP compared with controls. 23 Given that the average RRP patient receives around 4 surgeries every year, 1,24 it is unsurprising that the total annual cost for RRP-related healthcare nationally amounts to an estimated $120,000,000. 23,25 When considering that pulmonary RRP represents the most morbid, refractory manifestation of RRP, it is reasonable to assume that RRP patients with pulmonary involvement experience even greater quality of life impairments and medical costs, although no study directly investigating this question exists to date.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 The fiscal implications of RRP too are immense, with one study showing greater than $60,000 in a two-year cost difference for patients with RRP compared with controls. 23 Given that the average RRP patient receives around 4 surgeries every year, 1,24 it is unsurprising that the total annual cost for RRP-related healthcare nationally amounts to an estimated $120,000,000. 23,25 When considering that pulmonary RRP represents the most morbid, refractory manifestation of RRP, it is reasonable to assume that RRP patients with pulmonary involvement experience even greater quality of life impairments and medical costs, although no study directly investigating this question exists to date.…”
Section: Discussionmentioning
confidence: 99%
“…23 Given that the average RRP patient receives around 4 surgeries every year, 1,24 it is unsurprising that the total annual cost for RRP-related healthcare nationally amounts to an estimated $120,000,000. 23,25 When considering that pulmonary RRP represents the most morbid, refractory manifestation of RRP, it is reasonable to assume that RRP patients with pulmonary involvement experience even greater quality of life impairments and medical costs, although no study directly investigating this question exists to date. Our study, however, provides preliminary evidence for this notion, with our cohort of pulmonary RRP patients receiving an average of nearly 7 surgeries per year before induction of systemic bevacizumab, which is greater than what has been previously reported for non-pulmonary RRP cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a randomized controlled trial of 2-dose bivaalent (Cervarix) vaccination in girls aged 4-6 years, the vaccine had an acceptable safety profile as well as producing a high and sustained immunological response during 30 months of follow-up (20). A study conducted in USA concluded in very high direct costs of treating new cases of juvenile RRP and suggested to consider its results in HPV vaccination promotion investment decisions (21). The 2020, the world health organization (WHO) Global Strategy recommends that HPV vaccines should be included in all national immunization programs and should reach 90% of all girls by age 15 by 2030 (22).…”
Section: F O R P U B L I C a T I O Nmentioning
confidence: 99%
“…With the advent of vaccinations for HPV initially intended to reduce the morbidity and mortality of cervical cancer and genital warts, the incidence of RRP is rapidly changing but has previously been estimated to be 4.3 per 100 000 children and 1.8 per 100 000 adults 1 . The initial 2 year direct cost of treating RRP can be as high as $76 000 and the annual cost of all RRP patients has been estimated to be between $40‐123 million, which highlights the importance of prevention 10,11 . The most substantial improvements to our understanding of RRP have been made in prevention and adjuvant therapies which will be highlighted in this review.…”
Section: Introductionmentioning
confidence: 99%